Isolation and Identification Avian Influenza A non-H5 Virus from Muscovy Duck (Cairina moschata) at Two Live Bird Markets in Surabaya - karsari, deya (Stem Cell Research and Development Center, Universitas Airlangga, 2020)
The aim of this study was to isolate and identify Avian Influenza A non-H5 virus from muscovy duck at two live bird markets in Surabaya. Muscovy duck is the natural reservoir of Avian Influenza virus, in which all of the 16 HA subtypes and 9 NA maintained. The Avian Influenza virus replicates in intestinal tract of the reservoirs, causing the high amount of virus shed in the faeces. This study is an observational descriptive study, using non random sampling method of determined samples. The method used in this study were Hemagglutination Inhibition (HI) test and Enzyme Linked Immunosorbent Assay (ELISA) test. Avian Influenza A non-H5 virus was identified 19.23% (5 samples out of 26) in PS1 and 23.34% (7 samples out of 30) in PS2. This finding shows that Avian Influenza A non-H5 virus could be isolated and identified from muscovy duck at two live bird markets in Surabaya.